Utopia and Modernity in China Contradictions in Transition - Margolies, David; Cao, Qing (Pluto Press, 2022)
The contradictions of modernisation run through the whole of modern Chinese history. The abundance of manufactured goods being sold in the west attests to China's industrial revolution, but this capitalist vision of 'utopia' sits uneasily with traditional Chinese values. It is also in conflict with the socialism that has been the bedrock of Chinese society since the foundation of the People's Republic in 1949. Utopia and Modernity in China examines the conflicts inherent in China's attempt to achieve a 'utopia' by advancing production and technology. Through the lenses of literature, arts, law, the press and the environment, the contributors interrogate the contradictions of modernisation in Chinese society and its fundamental challenges. By unpicking both China's vision of utopia and its realities and the increasing tension between traditional Chinese values and those of the west, this book offers a unique insight into the cultural forces that are part of reshaping today's China.